Princess Mononoke [videorecording (DVD)] - Miyazaki, Hayao, 1941-; Miyazaki, Hayao, 1941- (Shout! Factory, 2017)
Searching to find the cure for a tatarigami's curse, Ashitaka travels the forests and becomes entangled in the bitter battles of the people that he meets.